Training to Create Smart Apps Creator (SAC) Learning Media and Differentiated Learning Materials to Improve the Competency of History Teachers - Oka Agus Kurniawan Shavab; Edi Fitriana Afriza; Iyus Jayusman; Zeyn Dwi Alfaridza Rifahma; Intan Amelia; Ferdy Muhammad Hakim; Rosinta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Based on the analysis of the problems found in the joint observation activities of the Garut Regency History MGMP, several priority problems were found that were to the partners' needs, including 1). There are still many history teachers who need to maximize their teacher competencies in learning activities, such as the creation of innovative digital-based learning media as an effort to develop themselves and learning materials; 2). The implementation of differentiated learning carried out by members of the Garut Regency History MGMP still needs to meet the three elements of differentiation, namely differentiation of content, process, and product. This community service activity aims to train history teachers of MGMP Garut Regency in creating innovative learning media based on Smart Apps Creator (Sac) integrated with differentiated learning and gamification. The methods implemented were Observation of problems and interviews of factual conditions with partners of the Garut Regency History MGMP, Socialization & training in developing competencies in understanding, knowledge, and skills of differentiated learning, and Socialization & training in creating integrated Smart Apps Creator (SAC) learning media with gamification and differentiated teaching materials to improve teacher competency.The results of this activity show that the organizational management skills of MGMP History teachers of Garut Regency are 61% to 92%. Meanwhile, the skills of history teachers increased from 61% to 91%. The training activities carried out are a real solution for history teachers to solve their problems.